Peripheral cytopenia in children: a hospital-based study - Gupta, Aditi; Bhatnagar, Ruchika; Prasad, P. L. (International Journal of Contemporary Pediatrics, 2019)
Background: Peripheral cytopenia with its ramifications as pancytopenia and bicytopenia is a common hematological phenomenon in children. Its etiology ranging from benign self-limiting illness to severe life-threatening conditions decide the management and prognosis in these children. This study aims to describe the clinical, haematological and etiological profile of peripheral blood cytopenia in children of Rohilkhand region. Methods: A hospital based prospective observational study conducted in the Pediatric ward of a teaching hospital over a period of 30 months. All children between age 6 months to 14 years with bicytopenia and pancytopenia on hemogram were included. Detailed history, clinical examination, haematological tests followed by bone marrow aspiration wherever indicated was performed. Additional tests like parasitological and sepsis work up was undertaken on case to case basis, to ascertain the cause of cytopenia. Results: Bicytopenia was more common than pancytopenia (61.2% vs. 38.8%) The most common age group observed was 10-14 years. Normocytic normochromic blood picture was seen in all cases of cytopenia while macrocytic normochromic blood picture had statistically significant association with pancytopenia. Fever was the commonest symptom, while pallor was the commonest sign followed by hepatosplenomegaly. Most common etiology in bicytopenia was infective (68%) while pancytopenia reported equal incidence of infective (50%) and non-infective causes. Malaria was the commonest infective cause of bicytopenia (46.3%) and pancytopenia (27%). Children with bicytopenia had higher incidence of malignancy (22% vs. 7.7%) and lesser incidence of nutritional causes (7.3% vs. 27%), and aplastic anemia (2.4% vs. 15.4%) as compared to pancytopenia. Conclusions: Clinical assessment coupled with haematological tests plays a pivotal role in ascertaining the cause of cytopenia in children. As the etiologies are varied, their knowledge and distribution unique to a particular region may help in better management and outcome.